Religious Diversity and Muslim Family Law: A Socio-Legal Study of Sunni–Shia Marriage in Indonesia - Umar Umar; Muhammad Faisol; Lutfi Nur Cahyo (Al-Qalam Institue, 2026)
This study examines Sunni–Shia marriage in Indonesia as a socio-legal phenomenon situated within the broader context of religious diversity and Muslim family law. Although Indonesian Islamic family law formally recognizes marriage between Sunni and Shia Muslims, social acceptance of such marriages remains contested in many Muslim communities. Using a qualitative empirical method with a socio-legal approach, this research explores the experiences of Sunni–Shia couples in Bondowoso, East Java, focusing on religious negotiation, social dynamics, and the interaction between formal law and communal norms. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis integrated with the framework of maqāṣid al-sharī‘ah. The findings reveal that Sunni–Shia marriages are characterized by continuous processes of adaptation and negotiation within family and social life. Couples frequently develop strategies of compromise regarding religious practices, child upbringing, and communal interaction in order to maintain family harmony. However, many also experience social stigma, communal suspicion, and challenges related to sectarian identity. From the perspective of maqāṣid al-sharī‘ah, the phenomenon reflects an ambivalent relationship between maṣlaḥah and mafsadah, particularly concerning the protection of religion, emotional well-being, and lineage. The study concludes that Sunni–Shia marriage illustrates the dynamic operation of legal pluralism within Indonesian Muslim society and highlights the importance of contextual and inclusive approaches in contemporary Muslim family law.